2006
DOI: 10.1111/j.1471-4159.2006.04307.x
|View full text |Cite
|
Sign up to set email alerts
|

Luteinizing hormone receptor mediates neuronal pregnenolone production via up‐regulation of steroidogenic acute regulatory protein expression

Abstract: The functional consequences of luteinizing hormone/human chorionic gonadotropin signaling via neuronal luteinizing hormone/human chorionic gonadotropin receptors expressed throughout the brain remain unclear. A primary function of luteinizing hormone (LH) in the gonads is the stimulation of sex steroid production. As LH can cross the blood-brain barrier, present in cerebrospinal fluid and is expressed by neuronal cells, we tested whether LH might also modulate steroid synthesis in the brain. Treatment of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 83 publications
2
39
0
Order By: Relevance
“…Irrespective, these data support the use of leuprolide acetate in the treatment of AD; leuprolide acetate has been shown in clinical trials to stabilize cognition in women with mild-to-moderate AD over a 1 year period (LaPlante et al 2006). Thirdly, neuronal LH might impact neurosteroid production, since we have recently demonstrated that LH promotes neurosteroid production in human neuroblastoma cells and in differentiated rat primary neurons (Liu et al 2006). Future studies will therefore be important in determining the exact role of neuronal LH.…”
Section: Functional Consequences Of Gnrh I Induction Of Lh Expressionmentioning
confidence: 99%
“…Irrespective, these data support the use of leuprolide acetate in the treatment of AD; leuprolide acetate has been shown in clinical trials to stabilize cognition in women with mild-to-moderate AD over a 1 year period (LaPlante et al 2006). Thirdly, neuronal LH might impact neurosteroid production, since we have recently demonstrated that LH promotes neurosteroid production in human neuroblastoma cells and in differentiated rat primary neurons (Liu et al 2006). Future studies will therefore be important in determining the exact role of neuronal LH.…”
Section: Functional Consequences Of Gnrh I Induction Of Lh Expressionmentioning
confidence: 99%
“…GnRH receptors (GnRHRs) have been localized in many regions of the brain such as the hippocampus and cortex and detected in human neuronal cell models like the neuroblastoma SH-SY5Y and M17 cells [16,17]. In M17 cells GnRH induces an up-regulation of the LH␤ subunit [17] and LH mediates neuronal pregnenolone production increasing Steroidogenic Acute Regulatory protein (StAR) expression [18]. Moreover, GnRH regulates estrogen synthesis and spine synapse density in rat primary hippocampal cultures [19].…”
Section: Introductionmentioning
confidence: 99%
“…38,39 The live cells were counted using trypan blue exclusion assay in a hemocytometer. The SNF substrates on the coverslips were placed under the ultraviolet radiation overnight before use.…”
Section: Primary Rat Hippocampal Neuron Culturementioning
confidence: 99%